2015
DOI: 10.1177/0194599815573224
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Hypertrophy of the Lingual Tonsils

Abstract: LTH does not seem to be associated with OSAHS or BMI in this group of patients. High RSI, younger age, and gender may be factors associated with increased lingual tonsil thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
6
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 12 publications
(25 reference statements)
2
32
6
2
Order By: Relevance
“…There appears to be a complex interplay with laryngopharyngeal reflux (LPR) emerging as a strong potential contributor to LTH and, subsequently, OSA. Previous authors have also demonstrated an association between LTH and OSA, BMI, age and smoking, but there has not been general agreement [1, 7]. This study adds further support to an association between a positive reflux finding score and BMI with lingual tonsil hypertrophy, but does not support a history of childhood tonsillectomy or age being associated with lingual tonsil size in adults.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…There appears to be a complex interplay with laryngopharyngeal reflux (LPR) emerging as a strong potential contributor to LTH and, subsequently, OSA. Previous authors have also demonstrated an association between LTH and OSA, BMI, age and smoking, but there has not been general agreement [1, 7]. This study adds further support to an association between a positive reflux finding score and BMI with lingual tonsil hypertrophy, but does not support a history of childhood tonsillectomy or age being associated with lingual tonsil size in adults.…”
Section: Discussioncontrasting
confidence: 70%
“…A trend was also seen for a negative correlation with age, but was not statistically significant. This association has also been supported by Friedman’s group in Chicago, where a statistically significant association was found between increasing LTH and decreasing age, RSI >10 and positive smoking status [7]. Interestingly, they did not, however, find an association with BMI, PPI use or allergy medication use.…”
Section: Discussionsupporting
confidence: 65%
“…Lingual tonsil hypertrophy (LTH) is a clinical condition often observed in clinical practice during the inspection of the tongue base region . This lymphatic hypertrophy (LH) is implicated in a variety of airway pathologies, ranging from sleep‐related breathing disorders, lingual tonsillitis, and difficult intubation procedures . Additionally, it is frequently a cause of foreign body sensation in the throat and of pharyngodynia in cases of it inflammation …”
Section: Introductionmentioning
confidence: 99%
“…The etiology regarding the growth of this lymphatic tissue (LT) has not been clearly proved . The few studies about this topic showed that previous adenotonsillectomy, laryngopharyngeal reflux (LPR), and a high body mass index could be correlated to LTH, even if defined data regarding this aspect are not available …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation